Development of Design and Control Manipulator Arm on Hexapod Robot with Smart Vision Sensor - Gralo Yopa Rahmat Pratama; Nuryono Satya Widodo (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
In 2021, the Indonesian Search and Rescue Robot Competition underwent significant changes, transitioning from its original name of "Firefighting Robot Contest" to "Search and Rescue Robot Contest." With existing regulations and new races, this robot used in the Indonesian Search and Rescue Robot Contest is an essential addition manipulator robot arm to finish mission victim rescue. With existing study about Design Development and Control Manipulator Arm on this Hexapod Robot with Smart Vision Sensor expected can help the development of the AL-JAZARI team's hexapod robot in mission victim rescue. Research, This does development design and control from a manipulator robot arm that can save victims in the rules of the Indonesian Search and Rescue Robot Contest. This uses input from the Pixy Camera, and its output is from the movement of the manipulator arm of the MG90S servo, which can save the orange victim. A Pixy Camera detects the victim and is picked up by a robotic arm. The manipulator's arm uses the MG90S servo as the actuator. In contrast, the buffer from the servo uses a 3D print designed to adapt to robotic bodies and efficiently, at times, save victims. Result study This robot can run on the victim rescue track by pushing the start button, then the robot will move autonomously with level success casualty rescue by 85% at good lighting and level lighting success dim by 80%.